Fe monatomic catalyst material with nitrate reduction electro-catalysis performance and preparation method of Fe monatomic catalyst material

By Te doping the Fe-N4 site, Fe-Te bonds are formed, and the polarity of the catalytic site is enhanced, the problem of insufficient adsorption of polar intermediates by Fe-N4 site is solved, and the activity and selectivity of ammonia produced by electrocatalytic nitrate reduction is significantly improved.

CN119800413AActive Publication Date: 2025-04-11TSAKER CHEM (DONGYING) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510286125.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

The Fe-N4 site has weak adsorption of polar intermediates during the process of electrocatalytic nitrate reduction and ammonia production, resulting in lower reactive activity and selectivity.

Method used

By introducing Te elements, the Fe-N4 site is doped and modified to form Fe-Te bonds, breaking the geometric symmetry and enhancing the polarity of the catalytic site, thereby improving the adsorption and deep reduction of *HNO2 intermediates.

Benefits of technology

The activity and selectivity of the catalyst are significantly improved, the adsorption of polar intermediates is enhanced, and the performance of electrocatalytic nitrate reduction is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800413A_ABST
    Figure CN119800413A_ABST
Patent Text Reader

Abstract

The invention discloses a Fe monatomic catalyst material with an electro-catalysis nitrate reduction performance and a preparation method thereof, in particular to an electro-catalyst with a Te-doped Fe-N4 material loaded on graphene and a preparation method thereof, Te and Fe are gradually doped to zinc nitrate and 2-methylimidazole to form ZIF-8, high-temperature pyrolysis is carried out, and the Fe monatomic catalyst material with the electro-catalysis nitrate reduction performance is obtained. The catalyst with a Fe-N3Te catalytic site structure is formed, and the micro shape of the catalyst is an irregular hexagon after the catalyst is calcined. Te doping modification is carried out on a traditional Fe-N4 site, and the original geometric symmetry is changed, so that adsorption of a polar intermediate by a catalytic site is enhanced, the energy barrier of the catalytic site is reduced, and the activity and selectivity of the catalyst are improved. The catalyst can pass sixteen cycle tests, has good stability, is simple in preparation method, can effectively convert nitrate pollutants in sewage, and has a large-scale application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of single-atom catalyst materials for electrocatalytic nitrate reduction to produce ammonia, and more specifically, to an Fe-N4 site-modified electrocatalytic material and a preparation method thereof, that is, an Fe single-atom catalyst material with electrocatalytic nitrate reduction performance and a preparation method thereof. Background Art

[0002] Ammonia (NH3) is an important raw material for the production of amino fertilizers. The current global annual demand for ammonia is 150 million tons, and by 2023, China's demand will reach more than 60 million tons, and the market demand is huge. At present, industrial ammonia synthesis mainly uses the Haber-Bosch process, but this process consumes a lot of energy and requires high temperature (400-500 °C) and high pressure (150-250 atm). According to statistics, the Haber-Bosch process accounts for 1%-2% of the total global energy consumption and emits about 4 billion tons of carbon dioxide each year. Its heavy carbon footprint has brought corresponding pressure on energy and environmental protection. Therefore, it is very important to find an emerging green and mild method for synthesizing ammonia to replace existing technologies.

[0003] Electrocatalytic ammonia synthesis is divided into electrocatalytic nitrogen reduction to ammonia (NRR) and electrocatalytic nitrate reduction to ammonia (NO3RR). However, the nitrogen-nitrogen triple bond energy of nitrogen molecules (941 kJ mol −1 ) is high and difficult to break; at the same time, the solubility of nitrogen in aqueous solution is low, resulting in a low ammonia production rate in this reaction. In contrast, N=O (204 kJ mol -1 )The lower dissociation energy and higher solubility of nitrate make NO3RR easier to drive than NRR. In addition, NO3RR can simultaneously achieve the treatment of nitrate as a water pollutant. In recent years, improper treatment of industrial wastewater and excessive use of fertilizers have led to excessive nitrate concentrations in wastewater, which may disrupt the balance of aquatic ecosystems and cause human diseases such as methemoglobinemia, blue baby syndrome and even cancer. At present, the main methods for treating water-soluble nitrate pollutants are ion exchange, biological denitrification, electrodialysis, reverse osmosis, etc. However, these methods have problems such as low efficiency, serious secondary pollution, and high energy consumption, making it difficult to further promote them. Therefore, electrocatalytic nitrate reduction to ammonia is a very promising method for synthesizing ammonia, taking into account the two important aspects of environmental protection and energy saving, so the development of efficient NO3RR catalysts is of great significance.

[0004] In recent years, single-atom catalysts with metal-N4 sites dispersed on nitrogen-doped carbon have the highest atomic utilization and structural stability, such as Fe-N4 sites and Cu-N4 sites, and these sites show good electrocatalytic activity for NO3RR. NO3RR is a complex electrocatalytic reduction process with 8 electrons and 9 protons. Designing efficient catalytic sites, enhancing their adsorption of nitrate intermediates (*HNO2), promoting the deep reduction of intermediates (*HNO2) instead of desorption, reducing the formation of toxic byproduct nitrite, and improving the selectivity of ammonia as the main product and catalytic activity are all key scientific issues that need to be solved. However, metal-N4 sites are geometrically symmetrical and have weak adsorption of polar intermediates during electrocatalysis. Their catalytic activity and selectivity need to be improved. Therefore, how to effectively enhance the polarity of metal-N4 sites and thus enhance their adsorption of *HNO2 intermediates is an effective method to improve the activity and selectivity of catalytic sites for NO3RR, but it is challenging.

[0005] The present invention adopts Te element to dope and modify Fe-N4 site to form Fe-Te bond, thereby breaking the geometric symmetry of Fe-N4 site, enhancing the polarity of catalytic site, improving its adsorption of reaction intermediate *HNO2, making it further deeply reduced instead of desorbed, thereby improving the activity and selectivity of the catalyst. Summary of the invention

[0006] The purpose of the present invention is to provide an Fe single-atom catalyst material with electrocatalytic nitrate reduction performance and a preparation method thereof, which can solve the problems of weak adsorption of polar intermediates, low reaction activity and selectivity of single-atom catalysts at Fe-N4 sites in the process of electrocatalytic nitrate reduction to ammonia, effectively improve the polarity of the catalytic site, enhance the adsorption of polar intermediates at the catalytic site, and improve the catalytic activity and selectivity of electrocatalytic nitrate reduction to ammonia; the present invention has the advantages of simple preparation process and low cost, and has significantly improved the electrocatalytic nitrate reduction performance, and is expected to be further industrialized in the fields of nitrate wastewater treatment and synthetic fertilizers.

[0007] In order to solve the above technical problems, the present invention is implemented by the following technical solutions: A Fe single-atom catalyst material with electrocatalytic nitrate reduction performance, namely Fe-N3Te / CN material, includes Fe-N3Te as a catalytic site and a graphene carrier mainly composed of carbon and nitrogen (the mass ratio of carbon to nitrogen is 1:7~1:10), presenting a hexagonal structure.

[0008] The diameter of Fe single atom in the Fe-N3Te / CN material is 0.1-0.3 nm; The diameter of Te single atom in the Fe-N3Te / CN material is 0.1-0.3 nm.

[0009] The Fe-N3Te / CN material has a diameter of 200-500 nm.

[0010] In the Fe-N3Te / CN, a Te atom is introduced next to the Fe atom to form a Fe-Te chemical bond.

[0011] A method for preparing an Fe single-atom catalyst material having electrocatalytic nitrate reduction performance, comprising preparing a Te / ZIF-8 material, preparing a Fe-Te / ZIF-8 material, and preparing a Fe-N3Te / CN material, specifically: (1) Add Zn(NO3)2·6H2O and Te powder to methanol and dissolve them, which is referred to as solution A. Prepare a 2-methylimidazole methanol solution, which is referred to as solution B. Quickly pour solution B into solution A, stir at room temperature for 6-48 hours, centrifuge, wash with ethanol three times, and dry at 45-65 °C overnight to obtain Te / ZIF-8. (2) Adding DMF to the Te / ZIF-8 prepared in step (1) to dissolve, which is referred to as liquid C; adding DMF to ferric acetylacetonate to dissolve, which is referred to as liquid D; adding liquid D to liquid C, stirring, centrifuging, washing, and drying to obtain Fe-Te / ZIF-8 powder; (3) The Fe-Te / ZIF-8 prepared in step (2) is heated and pyrolyzed at high temperature to obtain black powder Fe-N3Te / CN.

[0012] In the step (1), the molar ratio of Zn(NO3)2·6H2O to Te powder is 5:16-10:1.

[0013] In the step (1), 75-300 mL of methanol is added to 2.97-11.90 g of Zn(NO3)2·6H2O and 0.5-4 g of Te powder.

[0014] The molecular weight of Te / ZIF-8 in step (1) is 357.2.

[0015] In the step (1), the size of the Te / ZIF-8 material is 200-500 nm.

[0016] The radius of Te atoms in the liquid A in step (1) is 0.97 Å.

[0017] In the step (1), methanol is added to Zn(NO3)2·6H2O and Te powder, and then ultrasonicated for half an hour to dissolve them.

[0018] The molar concentration of the 2-methylimidazole methanol solution in step (1) is 0.0375-0.150 mol / L.

[0019] In the step (1), 75-300 mL of methanol is added to 3.08-12.32 g of 2-methylimidazole to prepare a 2-methylimidazole methanol solution.

[0020] In the step (1), methanol is added to 2-methylimidazole and then ultrasonicated for half an hour to dissolve it.

[0021] In the step (1), liquid B is quickly poured into liquid A at a volume ratio of 1:1.

[0022] In the step (1), liquid B is quickly poured into liquid A, stirred at room temperature for 6-48 hours, centrifuged, washed with ethanol three times, and dried at 45-65 °C overnight to obtain Te / ZIF-8.

[0023] In the step (2), 25-100 mL of DMF is added to 0.25-1 g of Te / ZIF-8 prepared in the step (1).

[0024] In the step (2), after adding DMF to Te / ZIF-8, ultrasonic treatment is performed for 0.5-1 hour to dissolve it.

[0025] In the step (2), 25-100 mL of DMF is added to 0.25-1 g of ferric acetylacetonate.

[0026] In the step (2), after adding DMF to the ferric acetylacetonate, ultrasonic treatment is performed for 0.5-1 hour to dissolve it.

[0027] In the step (2), solution D is added to solution C, stirred at room temperature for 6-48 hours, centrifuged, washed with ethanol three times, and dried to obtain Fe-Te / ZIF-8 powder.

[0028] The size of Fe single atoms in the Fe-Te / ZIF-8 material in step (2) is 0.1-0.3 nm.

[0029] In the step (3), the Fe-Te / ZIF-8 is placed in a porcelain boat and heated in a tubular furnace.

[0030] The high temperature pyrolysis temperature in step (3) is 800-1200 °C.

[0031] The heating rate of the high temperature pyrolysis in step (3) is 2 °C·min -1 .

[0032] The holding time of high temperature pyrolysis in step (3) is 1-5 hours.

[0033] The high-temperature pyrolysis in step (3) is carried out in an inert atmosphere.

[0034] In the step (3), the high temperature pyrolysis is carried out in an argon atmosphere.

[0035] A Fe single-atom catalytic material with electrocatalytic nitrate reduction performance is used for electrocatalytic reduction of nitrate to produce ammonia.

[0036] A Fe single-atom catalytic material with electrocatalytic nitrate reduction performance is used for nitrate wastewater treatment and synthetic fertilizers.

[0037] An application method of a Fe single-atom catalytic material having electrocatalytic nitrate reduction performance: Fe-N3Te / CN powder is added to ethanol and water to form a uniform ink-like black solution; the solution is evenly coated on carbon paper and dried to serve as an electrocatalytic working electrode.

[0038] The beneficial effects of the present invention are: 1. The Fe single-atom catalyst material of the present invention is mainly composed of nitrogen-doped carbon graphene materials with irregular hexagons, which breaks the original geometric pair-forming structure of Fe-N4. Compared with the traditional Fe-N4 site, the polarity of the catalytic site of the catalyst material is increased, which greatly increases the adsorption of polar intermediates by the catalytic site, can optimize the activity and selectivity of the catalyst, and significantly improve the performance of the catalyst.

[0039] 2. The Fe single-atom catalyst material of the present invention also carries Te single atoms to form Fe-Te bonds, which are loaded on graphene materials on nitrogen-doped carbon. Nitrate reduction reaction is carried out at the Fe-Te single-atom site, which effectively improves the adsorption of polar intermediates at the catalytic site, allowing the nitrite intermediates to be further deeply reduced rather than desorbed.

[0040] 3. The preparation method of the Fe single-atom catalyst material of the present invention has a simple operation process, does not require large-scale instruments and equipment, and is economically feasible; at the same time, its preparation process is highly controllable and has excellent performance in electrocatalytic nitrate reduction to produce ammonia.

[0041] 4. The Fe single-atom catalyst material of the present invention can be used as a highly efficient electrocatalytic material, specifically for the electrocatalytic reduction of nitrates to produce ammonia, which can efficiently convert nitrates in industrial wastewater into more valuable ammonia, effectively solving the current problems of high energy consumption in nitrate wastewater treatment and ammonia production. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the XRD pattern of Fe-N3Te / CN in Example 1.

[0043] Figure 2This is the TEM image of Fe-N3Te / CN in Example 1, with a scale of 2-200 nm.

[0044] Figure 3 This is the mapping image corresponding to the spherical aberration electron microscope of Fe-N3Te / CN in Example 1.

[0045] Figure 4 This is the LSV diagram of the electrocatalytic nitrate production of ammonia by Fe-N3Te / CN in Example 1.

[0046] Figure 5 This is a diagram of the Faraday efficiency and ammonia production rate of 16 cyclic tests of Fe-N3Te / CN in Example 1.

[0047] Figure 6 This is the selectivity diagram of 16 cyclic tests of Fe-N3Te / CN in Example 1.

[0048] Figure 7 is the LSV diagram of the catalyst prepared in Example 1-7. DETAILED DESCRIPTION

[0049] The present invention is further described in detail below through specific examples. The following examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.

[0050] Embodiment 1:

[0051] (1) Preparation of Te / ZIF-8 A methanol solution containing 0.133 M Zn(NO3)2·6H2O and 0.104 M Te powder was prepared by adding 150 mL of methanol to Zn(NO3)2·6H2O (5.58 g, 0.02 mol) and 2 g of Te powder, and sonicating for half an hour to dissolve it, which was recorded as solution A; a methanol solution containing 0.5 M 2-methylimidazole was prepared by adding 150 mL of methanol to 2-methylimidazole (6.16 g, 0.075 mol), and sonicating for half an hour to dissolve it, which was recorded as solution B; solution B was quickly poured into solution A at a volume ratio of 1:1, stirred at room temperature for 24 hours, centrifuged, washed three times with ethanol, and dried at 50 °C overnight to obtain Te / ZIF-8.

[0052] (2) Preparation of Fe-Te / ZIF-8 0.5 g of Te / ZIF-8 prepared in step (1) was added with 50 mL of DMF and ultrasonicated for 1 hour to dissolve it, which was recorded as liquid C; 0.5 g of ferric acetylacetonate was added with 50 mL of DMF and ultrasonicated for 1 hour to dissolve it, which was recorded as liquid D. Liquid D was quickly added to liquid C, stirred at room temperature for 24 hours, centrifuged, washed with ethanol three times, and dried to obtain Fe-Te / ZIF-8 powder.

[0053] (3) Preparation of Fe-N3Te / CN The Fe-Te / ZIF-8 prepared in step (2) was placed in a porcelain boat and heated in a tube furnace at 920 °C, 2 °C min -1 , 3h, maintaining argon atmosphere, to obtain black powder Fe-N3Te / CN, which is a Fe single-atom catalytic material with electrocatalytic nitrate reduction performance, and the single atom diameter is 0.15 nm.

[0054] The molecular weight of Te / ZIF-8 in the above step (1) is 357.2.

[0055] In the above step (1), the diameter of the Te / ZIF-8 material is 200-500 nm.

[0056] The radius of Te atoms in liquid A in the above step (1) is 0.97 Å.

[0057] Figure 1 This is the XRD pattern of the Fe single atom catalyst prepared in Example 1. As shown in the XRD pattern, there are only two broad peaks assigned to the diffraction peaks of carbon (002)(100) / (101), which are 25° and 44° respectively, and no peaks related to iron-based substances are formed.

[0058] Figure 2 This is a TEM image of the Fe single atom catalyst in Example 1. As shown in the figure, no obvious nanoparticles are formed, and the diameter of Fe-N3Te / CN is 200-500 nm.

[0059] Figure 3 This is the spherical aberration electron microscope of Fe-N3Te / CN in Example 1 and the corresponding. As shown in the figure, the bright spots represent single Fe atoms or single Te atoms, and the mapping results show that C, N, Fe, and Te are distributed relatively evenly.

[0060] Table 1 Table 1 is the inductively coupled plasma emission spectrometer data of Fe-N3Te / CN in Example 1. It proves that the material does carry trace amounts of Fe and Te.

[0061] (4) Fe-N3Te / CN for electrocatalytic nitrate reduction to ammonia Weigh 8 mg of the Fe-N3Te / CN powder obtained in step (3), add 470 μL of ethanol and 470 μL of water, and sonicate for half an hour to make it a uniform ink-like black solution. Spread the solution evenly on a 2×2 cm 2 The carbon paper is dried and used as the working electrode for electrocatalysis. The electrochemical test part of the present invention adopts a three-electrode system, in which a platinum electrode is used as the counter electrode and an Ag / AgCl electrode is used as the reference electrode. The electrochemical performance is tested using Chenhua CHI-760E. The concentration of ammonia is quantitatively tested using a UV-visible spectrometer using a colorimetric method to calculate the Faraday efficiency, ammonia production rate and catalyst selectivity.

[0062] Figure 4 This is the LSV diagram of the electrocatalytic nitrate reduction to ammonia by Fe-N3Te / CN in Example 1. It can be observed that after adding potassium nitrate, the absolute value of the current density increases significantly, indicating that the catalyst can catalyze nitrate reduction.

[0063] Figure 5 Figure 1 shows the Faraday efficiency and ammonia production rate of Fe-N3Te / CN after 16 cycles. It can be seen from the figure that the catalyst has a relatively stable Faraday efficiency (average value of 94.6%) and ammonia production rate (average value of 1.95 mg h-1) after multiple cycles. -1 cm -2 ).

[0064] Figure 6 This is the selectivity diagram of 16 cyclic tests of Fe-N3Te / CN in Example 1. It can be seen from the figure that the catalyst has a high selectivity for deep reduction of nitrate to produce ammonia, with an average selectivity of 83.9%.

[0065] Figure 7 The electrocatalytic LSV test results of the catalysts prepared in Examples 1-7 are shown in FIG. Figure 7 It can be seen that the catalyst in Example 1 has the best performance.

[0066] Embodiment 2:

[0067] (1) Preparation of Te / ZIF-8 A methanol solution containing 0.133 M Zn(NO3)2·6H2O and 0.0261 M Te powder was prepared by adding 150 mL of methanol to Zn(NO3)2·6H2O (5.58 g, 0.02 mol) and 0.5 g Te powder, and sonicating for half an hour to dissolve it, which was recorded as solution A; a methanol solution containing 0.5 M 2-methylimidazole was prepared by adding 150 mL of methanol to 2-methylimidazole (6.16 g, 0.075 mol), and sonicating for half an hour to dissolve it, which was recorded as solution B; solution B was quickly poured into solution A at a volume ratio of 1:1, stirred at room temperature for 24 hours, centrifuged, washed three times with ethanol, and dried at 50 °C overnight to obtain Te / ZIF-8.

[0068] (2) Preparation of Fe-Te / ZIF-8 (0.5 g) 0.5 g of Te / ZIF-8 prepared in step (1) was added with 50 mL of DMF and ultrasonicated for 1 hour to dissolve it, which was recorded as liquid C; 0.5 g of ferric acetylacetonate was added with 50 mL of DMF and ultrasonicated for 1 hour to dissolve it, which was recorded as liquid D. Liquid D was quickly added to liquid C, stirred at room temperature for 24 hours, centrifuged, washed with ethanol three times, and dried to obtain Fe-Te / ZIF-8 powder.

[0069] (3) Preparation of Fe-N3Te / CN The Fe-Te / ZIF-8 prepared in step (2) was placed in a porcelain boat and heated in a tube furnace at 920 °C, 2 °C·min -1 , 3h, maintaining argon atmosphere, to obtain black powder Fe-N3Te / CN with a single atom diameter of 0.14 nm.

[0070] (4) Fe-N3Te / CN for electrocatalytic nitrate reduction to ammonia Weigh 8 mg of Fe-N3Te / CN powder obtained in step (3), add 470 μL of ethanol and 470 μL of water, and sonicate for half an hour to make it into a uniform ink-like black solution. Spread the solution evenly on a 2×2 cm 2 The carbon paper is dried and used as the working electrode for electrocatalysis. The electrochemical test part of the present invention adopts a three-electrode system, in which a platinum electrode is used as the counter electrode and an Ag / AgCl electrode is used as the reference electrode. The electrochemical performance is tested using Chenhua CHI-760E. The concentration of ammonia is quantitatively tested using a UV-visible spectrometer using a colorimetric method to calculate the Faraday efficiency, ammonia production rate and catalyst selectivity.

[0071] The catalyst LSV prepared in Example 2 is as follows Figure 7 As shown in Figure 2, its Faraday efficiency is 70.0% and the ammonia production rate is 1.01 mg h -1cm -2 .

[0072] Embodiment 3:

[0073] (1) Preparation of Te / ZIF-8 A methanol solution containing 0.133 M Zn(NO3)2·6H2O and 0.0522 M Te powder was prepared by adding 150 mL of methanol to Zn(NO3)2·6H2O (5.58 g, 0.02 mol) and 1 g of Te powder, and sonicating for half an hour to dissolve it, which was recorded as solution A; a methanol solution containing 0.5 M 2-methylimidazole was prepared by adding 150 mL of methanol to 2-methylimidazole (6.16 g, 0.075 mol), and sonicating for half an hour to dissolve it, which was recorded as solution B; solution B was quickly poured into solution A at a volume ratio of 1:1, stirred at room temperature for 24 hours, centrifuged, washed three times with ethanol, and dried at 50 °C overnight to obtain Te / ZIF-8.

[0074] (2) Preparation of Fe-Te / ZIF-8 50 mL DMF was added to 0.5 g of Te / ZIF-8 prepared in step (1), and the mixture was dissolved by ultrasonic treatment for 1 hour, which was recorded as liquid C. 50 mL DMF was added to 0.5 g of ferric acetylacetonate, and the mixture was dissolved by ultrasonic treatment for 1 hour, which was recorded as liquid D. Liquid D was quickly added to liquid C, and the mixture was stirred at room temperature for 24 hours, centrifuged, washed with ethanol three times, and dried to obtain Fe-Te / ZIF-8 powder.

[0075] (3) Preparation of Fe-N3Te / CN The Fe-Te / ZIF-8 prepared in step (2) was placed in a porcelain boat and heated in a tube furnace at 920 °C, 2 °C min -1 , 3h, maintaining argon atmosphere, to obtain black powder Fe-N3Te / CN with a single atom diameter of 0.16 nm.

[0076] (4) Fe-N3Te / CN for electrocatalytic nitrate reduction to ammonia Weigh 8 mg of Fe-N3Te / CN powder obtained in step (3), add 470 μL of ethanol and 470 μL of water, and sonicate for half an hour to make it into a uniform ink-like black solution. Spread the solution evenly on a 2×2 cm 2 The carbon paper is dried and used as the working electrode for electrocatalysis. The electrochemical test part of the present invention adopts a three-electrode system, in which a platinum electrode is used as the counter electrode and an Ag / AgCl electrode is used as the reference electrode. The electrochemical performance is tested using Chenhua CHI-760E. The concentration of ammonia is quantitatively tested using a UV-visible spectrometer using a colorimetric method to calculate the Faraday efficiency, ammonia production rate and catalyst selectivity.

[0077] The catalyst LSV prepared in Example 3 is as follows Figure 7 As shown in Figure 2, its Faraday efficiency is 73.5% and the ammonia production rate is 1.41 mg h -1 cm -2 .

[0078] Embodiment 4:

[0079] (1) Preparation of Te / ZIF-8 Same as Example 1.

[0080] (2) Preparation of Fe-Te / ZIF-8 Same as Example 1.

[0081] (3) Preparation of Fe-N3Te / CN The Fe-Te / ZIF-8 prepared in step (2) was placed in a porcelain boat and heated in a tube furnace at 970 °C, 2 °C min -1 , 3h, maintaining argon atmosphere, to obtain black powder Fe-N3Te / CN with a single atom diameter of 0.15 nm.

[0082] (4) Fe-N3Te / CN for electrocatalytic nitrate reduction to ammonia Weigh 8 mg of Fe-N3Te / CN powder obtained in step (3), add 470 μL of ethanol and 470 μL of water, and sonicate for half an hour to make it into a uniform ink-like black solution. Spread the solution evenly on a 2×2 cm 2 The carbon paper is dried and used as the working electrode for electrocatalysis. The electrochemical test part of the present invention adopts a three-electrode system, in which a platinum electrode is used as the counter electrode and an Ag / AgCl electrode is used as the reference electrode. The electrochemical performance is tested using Chenhua CHI-760E. The concentration of ammonia is quantitatively tested using a UV-visible spectrometer using a colorimetric method to calculate the Faraday efficiency, ammonia production rate and catalyst selectivity.

[0083] The catalyst LSV prepared in Example 4 is as follows Figure 7 As shown in Figure 2, its Faraday efficiency is 74.8% and the ammonia production rate is 1.56 mg h -1 cm -2 .

[0084] Embodiment 5:

[0085] (1) Preparation of Te / ZIF-8 Same as Example 2.

[0086] (2) Preparation of Fe-Te / ZIF-8 0.5 g of Te / ZIF-8 prepared in step (1) was added with 50 mL of DMF, and ultrasonicated for 1 hour to dissolve it, which was recorded as liquid C; 0.5 g of ferric acetylacetonate was added with 50 mL of DMF, and ultrasonicated for 1 hour to dissolve it, which was recorded as liquid D. Liquid D was added to liquid C, stirred at room temperature for 24 hours, centrifuged, washed with ethanol three times, and dried to obtain Fe-Te / ZIF-8 powder.

[0087] (3) Preparation of Fe-N3Te / CN The Fe-Te / ZIF-8 prepared in step (2) was placed in a porcelain boat and heated in a tube furnace at 970 °C, 2 °C min -1 , 3h, maintaining argon atmosphere, to obtain black powder Fe-N3Te / CN, the single element diameter is 0.14 nm.

[0088] (4) Fe-N3Te / CN for electrocatalytic nitrate reduction to ammonia Weigh 8 mg of the Fe-N3Te / CN powder obtained in step (3), add 470 μL of ethanol and 470 μL of water, and sonicate for half an hour to make it a uniform ink-like black solution. Spread the solution evenly on a 2×2 cm 2 The carbon paper is dried and used as the working electrode for electrocatalysis. The electrochemical test part of the present invention adopts a three-electrode system, in which a platinum electrode is used as the counter electrode and an Ag / AgCl electrode is used as the reference electrode. The electrochemical performance is tested using Chenhua CHI-760E. The concentration of ammonia is quantitatively tested using a UV-visible spectrometer using a colorimetric method to calculate the Faraday efficiency, ammonia production rate and catalyst selectivity.

[0089] The catalyst LSV prepared in Example 5 is as follows Figure 7 As shown in Figure 2, its Faradaic efficiency is 69% and the ammonia production rate is 1.12 mg h -1 cm -2 .

[0090] Embodiment 6:

[0091] (1) Preparation of Te / ZIF-8 Same as Example 3.

[0092] (2) Preparation of Fe-Te / ZIF-8 Same as Example 3.

[0093] (3) Preparation of Fe-N3Te / CN The Fe-Te / ZIF-8 prepared in step (2) was placed in a porcelain boat and heated in a tube furnace at 970 °C, 2 °C min -1, 3h, maintaining argon atmosphere, to obtain black powder Fe-N3Te / CN, the single element diameter is 0.16 nm.

[0094] (4) Fe-N3Te / CN for electrocatalytic nitrate reduction to ammonia Weigh 8 mg of Fe-N3Te / CN powder obtained in step (3), add 470 μL of ethanol and 470 μL of water, and sonicate for half an hour to make it into a uniform ink-like black solution. Spread the solution evenly on a 2×2 cm 2 The carbon paper is dried and used as the working electrode for electrocatalysis. The electrochemical test part of the present invention adopts a three-electrode system, in which a platinum electrode is used as the counter electrode and an Ag / AgCl electrode is used as the reference electrode. The electrochemical performance is tested using Chenhua CHI-760E. The concentration of ammonia is quantitatively tested using a UV-visible spectrometer using a colorimetric method to calculate the Faraday efficiency, ammonia production rate and catalyst selectivity.

[0095] The catalyst LSV prepared in Example 6 is as follows Figure 7 As shown in Figure 2, its Faraday efficiency is 75.9% and the ammonia production rate is 1.43 mg h -1 cm -2 .

[0096] Embodiment 7:

[0097] (1) Preparation of ZIF-8 A methanol solution containing 0.133 M Zn(NO3)2·6H2O was prepared by adding 150 mL of methanol to Zn(NO3)2·6H2O (5.58 g, 0.02 mol), and sonicating for half an hour to dissolve it, which was recorded as solution A; a methanol solution containing 0.5 M 2-methylimidazole was prepared by adding 150 mL of methanol to 2-methylimidazole (6.16 g, 0.075 mol), and sonicating for half an hour to dissolve it, which was recorded as solution B; solution B was quickly poured into solution A, stirred at room temperature for 24 hours, centrifuged, washed three times with ethanol, and dried at 50°C overnight to obtain ZIF-8.

[0098] (2) Preparation of Fe / ZIF-8 0.5 g of ZIF-8 prepared in step (1) was added with 50 mL of DMF and ultrasonicated for 1 hour to dissolve it, which was recorded as liquid C; 0.5 g of ferric acetylacetonate was added with 50 mL of DMF and ultrasonicated for 1 hour to dissolve it, which was recorded as liquid D. Liquid D was quickly added to liquid C, stirred at room temperature for 24 hours, centrifuged, washed with ethanol three times, and dried to obtain Fe / ZIF-8 powder.

[0099] (3) Preparation of Fe-N4 / CN The Fe / ZIF-8 prepared in step (2) was placed in a porcelain boat and heated in a tube furnace at 920 °C, 2 °C min -1 , 3 h, maintaining an argon atmosphere, and obtaining black powder Fe-N4 / CN with a single atom diameter of 0.15 nm.

[0100] (4) Fe-N3 / CN for electrocatalytic nitrate reduction to ammonia Weigh 8 mg of the Fe-N4 / CN powder obtained in step (3), add 470 μL of ethanol and 470 μL of water, and sonicate for half an hour to make it a uniform ink-like black solution. Spread the solution evenly on a 2×2 cm 2 The carbon paper is dried and used as the working electrode for electrocatalysis. The electrochemical test part of the present invention adopts a three-electrode system, in which a platinum electrode is used as the counter electrode and an Ag / AgCl electrode is used as the reference electrode. The electrochemical performance is tested using Chenhua CHI-760E. The concentration of ammonia is quantitatively tested using a UV-visible spectrometer using a colorimetric method to calculate the Faraday efficiency, ammonia production rate and catalyst selectivity.

[0101] The catalyst LSV prepared in Example 7 is as follows Figure 7 As shown in Figure 2, its Faraday efficiency is 59.2% and the ammonia production rate is 0.76 mg h -1 cm -2 .

[0102] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can make many forms of specific changes without departing from the scope of protection of the present invention and the claims, all of which fall within the scope of protection of the present invention.

Claims

1. An Fe single-atom catalyst material having electrocatalytic nitrate reduction performance, namely, Fe-N3Te / CN material, characterized in that It includes Fe-N3Te as a catalytic site and a graphene carrier mainly composed of carbon and nitrogen, presenting a hexagonal structure.

2. The Fe single-atom catalyst material having electrocatalytic nitrate reduction performance according to claim 1, characterized in that The carbon-nitrogen mass ratio is 1:7-1:10; The Fe-N3Te / CN material has a diameter of 200-500 nm; The diameter of Fe single atom in the Fe-N3Te / CN material is 0.1-0.3 nm; The diameter of Te single atom in the Fe-N3Te / CN material is 0.1-0.3 nm.

3. The Fe single-atom catalyst material having electrocatalytic nitrate reduction performance according to claim 1, characterized in that A single Te atom is introduced next to a single Fe atom to form a Fe-Te chemical bond.

4. A method for preparing a Fe single-atom catalyst material having electrocatalytic nitrate reduction performance, characterized in that It includes the following steps: (1) Add Zn(NO3)2·6H2O and Te powder to methanol and dissolve them, which is referred to as solution A. Prepare a 2-methylimidazole methanol solution, which is referred to as solution B. Quickly pour solution B into solution A, stir at room temperature for 6-48 hours, centrifuge, wash with ethanol three times, and dry at 45-65 °C overnight to obtain Te / ZIF-8. (2) Add DMF to the Te / ZIF-8 prepared in step (1) and dissolve it, which is referred to as liquid C; add DMF to ferric acetylacetonate and dissolve it, which is referred to as liquid D; Solution D was added to solution C, and Fe-Te / ZIF-8 powder was obtained after stirring, centrifugation, washing and drying; (3) The Fe-Te / ZIF-8 prepared in step (2) is heated and pyrolyzed at high temperature to obtain black powder Fe-N3Te / CN.

5. The method for preparing a Fe single-atom catalyst material having electrocatalytic nitrate reduction performance according to claim 4, characterized in that In the step (1), the molar ratio of Zn(NO3)2·6H2O to Te powder is 5:16-10:

1.

6. The method for preparing a Fe single-atom catalyst material having electrocatalytic nitrate reduction performance according to claim 4, characterized in that In the step (1), 75-300 mL of methanol is added to 2.97-11.90 g of Zn(NO3)2·6H2O and 0.5-4 g of Te powder; 75-300 mL of methanol is added to 3.08-12.32 g of 2-methylimidazole, and the mixture is dissolved by ultrasonic treatment for half an hour to prepare a 2-methylimidazole methanol solution; liquid B is quickly poured into liquid A, stirred at room temperature for 6-48 hours, centrifuged, washed with ethanol three times, and dried at 45-65 °C overnight to obtain Te / ZIF-8.

7. The method for preparing a Fe single-atom catalyst material having electrocatalytic nitrate reduction performance according to claim 4, characterized in that In the step (2), 25-100 mL DMF is added to 0.25-1 g of the Te / ZIF-8 obtained in the step (1), and the mixture is ultrasonically treated for 0.5-1 hour to dissolve the mixture; 25-100 mL DMF is added to 0.25-1 g of ferric acetylacetonate, and the mixture is ultrasonically treated for 0.5-1 hour to dissolve the mixture; liquid D is added to liquid C, and the mixture is stirred at room temperature for 6-48 hours, centrifuged, washed with ethanol three times, and dried to obtain Fe-Te / ZIF-8 powder.

8. The method for preparing a Fe single-atom catalyst material having electrocatalytic nitrate reduction performance according to claim 4, characterized in that In step (3), Fe-Te / ZIF-8 is placed in a porcelain boat and heated in a tube furnace. The high-temperature pyrolysis temperature is 800-1200 °C and the heating rate of the high-temperature pyrolysis is 2 °C·min -1 The holding time of high temperature pyrolysis is 1-5 hours, and the high temperature pyrolysis is carried out in an argon atmosphere.

9. Application of a Fe single-atom catalytic material having electrocatalytic nitrate reduction performance, characterized in that Used for electrocatalytic reduction of nitrates to produce ammonia.

10. Application of a Fe single-atom catalytic material having electrocatalytic nitrate reduction performance, characterized in that Used for nitrate wastewater treatment and synthetic fertilizers.

Citation Information

Patent Citations

  • Fe-N-C CATALYST, METHOD OF PREPARATION AND USES THEREOF

    US20210047741A1

  • Electrocatalytic Conversion of Nitrates and Nitrites to Ammonia

    US20240327997A1